Validation studies: validating new tools and adapting old ones to new contexts - Mohd Sidik, Sherina (CRC Press, 2019)
Validation studies determine the accuracy, dependability and consistency of a tool in measuring what it is supposed to measure. Validation of a tool which detects depression in the community should determine the accuracy of the tool to detect depression in the specified population and prove that it is measuring what it is supposed to measure and is consistent throughout its usage. Face validity' is confirmation from a group of experts or other stakeholders as to whether this tool appears to be a reasonable measure of the concept as they understand it. 'Content validity' checks whether all the items in the tool that should be included are included and identifies the relevance of each indicator and criterion. 'Construct validity' is the extent to which the items in the tool are as closely associated as expected, according to theory. 'Criterion-related validity' determines the ability of each criterion of the tool to measure accurately a specific concept or condition.